Topological nodal i-wave superconductivity in PtBi2 - CHANGDAR, SUSMITA; Suvorov, Oleksandr; Kuibarov, Andrii; Setti, Thirupathaiah; Shipunov, Grigory; Aswartham, Saicharan; Wurmehl, Sabine; Kovalchuk, Iryna; Koepernik, Klaus; Timm, Carsten; Büchner, Bernd; Fulga, Ion Cosma; et al. (Zenodo, 2024)
This repository contains data and codes used in our paper: "Topological nodal i-wave superconductivity in PtBi2". See the readme.txt file for more information.